Analysis of Payroll Accounting Information Systems at The Ministry of Religious Affairs Office in Surabaya City - Wulansari, Yuli Yanti; Nurromadhoni, Dewi; Azhari, Muhammad (Journal of Applied Management and Business, 2024)
The Surabaya City Ministry of Religion Office is responsible for managing governmental duties in the religious sector. This research aims to analyze how the accounting information system for State Civil Apparatus (ASN) employee payrolls is applied in this office. This study is qualitative in nature, utilizing both primary and secondary data sources. Data were collected through interviews, observations, and documentation to provide a certain challenges remain. Common issues include outdated data in employee decrees and insufficient updates from employees, particularly regarding their children’s education status. The research suggests several improvements, including enhancing human resources involved in the payroll system to facilitate a quicker understanding and application of updated government regulations related to ASN payroll. Additionally, conducting regular training for system users and scheduling routine audits on employee data could improve system efficiency. Improving the payroll accounting information system at the Surabaya Ministry of Religion Office is essential, and one recommendation is to implement a notification system to remind employees to update relevant data, such as decree information and children’s educational status, to maintain data accuracy effectively.